UTILIZING ZUHD HADITHS FOR UPPER-CLASS CRIME PREVENTION - Wahid, Abd.; Ibrahim, Mazlan; Shomad, Bukhori Abdul; Nirwana AN, Andri; Damanhuri, Damanhuri (Universitas Islam Negeri Ar-Raniry, 2023)
Crime is becoming more widespread, with varied motives and often involving influential elites. The consequences of crimes committed by these elites are enormous, affecting not only themselves but also their families, institutions, and others. Therefore, addressing the increasing crime committed by influential elites requires efforts focused on prevention rather than just heavy punishment. One potential solution is through a religious approach, particularly by referencing the hadiths of Prophet Muhammad (SAW). Several hadiths teach the concept of Zuhd, which emphasizes avoiding excessive wealth accumulation and enjoying giving and sharing blessings with others. This article aims to present the Prophet’s teachings on leading a humble life and not excessively valuing wealth. The study employed qualitative research methods, including a literature review of relevant library sources. As a result, this article emphasizes that the Prophet taught that the orientation of human life should not solely focus on fulfilling worldly demands but also on having faith in the afterlife. Prophet Muhammad (SAW) exemplified Zuhd in his life, and his example needs to be emulated in the modern world today. Elite individuals who embody Zuhd will be more capable of restraining themselves from committing crimes while fulfilling their duties. This is because the attribute of Zuhd encourages everyone capable of committing a crime to refrain from doing so.